The Relationship Between Cognitive Style and Visual Spatial Intelligence of First Year Architectural Students - Erkan Yazıcı, Yasemin (My University, 2017)
This paper investigates the relationship between the cognitive styles and visual spatial intelligence of freshman students of architecture. Cognitive styles of the students were determined using the “levels” dimension of the Thinking Styles Inventory. The assessment of the 2D and 3D perception skills of the students was based on their performance in answering a series of questions on 3D projections and perspective drawings. The performance of students at answering the questions was found to be significantly related to their cognitive styles. The students with local cognitive style were found to have more advanced spatial perception skills in comparison to the students with global cognitive style.

Bu çalışmada, ilk yıl mimarlık öğrencilerinin bilişsel stilleri ile görsel uzamsal zekâları arasındaki ilişki incelenmektedir. Öğrencilerin bilişsel stilleri, Düşünme Stilleri Envanteri’nin “seviyeler” boyutu kullanılarak tespit edilmiştir. Öğrencilerin 2 ve 3 boyutlu algı becerileri, 3 boyutlu objelerin izdüşüm ve perspektif çizimleri ile ilgili bir dizi soruyu yanıtlamada gösterdikleri performanslarına bağlı olarak belirlenmiştir. Öğrencilerin soruları yanıtlamadaki performansları ile bilişsel stilleri arasında önemli ölçüde bağlantı olduğu görülmüştür. Ayrıntıcı bilişsel stile sahip öğrencilerin uzamsal algı becerilerinin bütüncü bilişsel stile sahip olanlara göre daha gelişmiş olduğu tespit edilmiştir.
İlk Yıl Mimarlık Öğrencilerinin Bilişsel Stilleri İle Görsel Uzamsal Zekaları Arasındaki İlişki
Keywords: Architectural Design Education; Cognitive Style; First Year Architecture Education; Thinking Styles Inventory; Visual Spatial Intelligence; Mimari Tasarım Eğitimi; Bilişsel Stil; İlk Yıl Mimarlık Eğitimi; Düşünme Stilleri Envanteri; Görsel Uzamsal Zeka